Immigrant Labour Markets, 1988 - Makkai, Toni (ADA Dataverse, 2019)
This study incorporates statistics pertaining to industrial location and employers of respondents surveyed in the Issues in Multicultural Australia, 1988 survey (SSDA No 534-540, Office of Multicultural Affairs, 1988). Data from the Issues in Multicultural Australia, 1988 survey are included in this dataset. Industry variables include industry code; gross wage and salaries; severance payments; payroll tax; contributions to super; workers compensation; major labour costs; new fixed cap expenditures; location counts; management units; enterprise concentration ratios; establishment concentration ratios; wages concentration ratios; turnover concentration ratios; value added concentration ratios and turnover concentration ratios. Enterprise variables include number of enterprises and employees; turnover; expenses; rent, leasing and hiring revenue; insurance and compensation premiums; interest and royalties paid; and fixed capital expenditure. Company and annual report data variables include annual sales; number of employees; imports and exports; type of company; operating revenue and profits and total assets. Employment variables include number of union members employed and number of full-time and part-time employees. Variables from the Issues in Multicultural Australia, 1988 include country of birth and parents' country of birth, father's occupation and educational level; language - English language ability, languages spoken, use of own language, ethnicity - identification with ethnic groups, government aid to such groups, religious observance; education - school leaving age, qualifications obtained, recognition of overseas qualifications, transition to employment; current job - job status, occupation, industry, trade union membership, gross income, problems looking for work; spouse - country of birth, education and qualifications, occupation and industry, income and income sources; immigration - attitudes to immigration policy, opportunities for immigrants, social distance from various ethnic groups, and attitudes to authority; family and social networks - numbers of children, siblings in Australia, numbers of close friends in Australia, neighbours; citizenship - citizenship status, participation in political matters and interest in politics; trust in government; and multiculturalism - views on what multiculturalism means, and its importance to Australian society.